(untitled) (Indian Journal of Animal Production and Management, 2024)
The present experiment was conducted in an organized herd of lactating Gir cows during April, 2017 and October, 2018. Milk samples were collected from each quarter at monthly interval, checked for sub clinical mastitis by California Mastitis Test (CMT) as a routine practice and analyzed for milk constituents. Total 1000 milk samples, negative for CMT were purposively included for the study to see the effect of season (winter, summer and rainy), stage of lactation (early, mid and late) and parity (1st, 2nd-3rd and ≥4) on milk constituents and to study association among different milk constituents. The overall milk fat, solid not fat (SNF), protein, lactose and total solid (TS) percent were 4.111±0.020, 8.625±0.028, 3.180±0.011, 4.731±0.015 and 12.737±0.047%, respectively. There was significant (p≤0.05) effect of season on all milk constituents (fat, SNF, protein and TS) except milk lactose. The concentrations of milk constituents were significantly (p≤0.05) higher during rainy season as compared to winter season. Milk constituents were affected significantly (p≤0.05) by the stage of lactation and parity of cows. Milk samples from early stage of lactation comprised of significantly (p≤0.05) higher level of milk constituents than mid and late lactation stages. Significantly (p≤0.05) higher level of milk constituents were observed in 1st parity cows compared to other parities cows. There was significant (p≤0.001) positive correlation among different milk constituents. On the basis of findings it can be concluded that season, stage of lactation and parity affect milk constituents of Gir cows, while the positive association among milk constituents indicated that improvement of one trait could improve the other traits.